Were there losses in social support during the pandemic? Testing the impact of COVID-19 on psychological adjustment to trauma in United States adults - Mitchell, Benjamin J.; Gawlik, Emily A.; Baugher, Brittany J.; George, Richard L.; Muakkassa, Farid F.; Mallat, Ali F.; Gunstad, John; Delahanty, Douglas L.; Coifman, Karin G. (Frontiers in Psychology, 2022)
Introduction Social support is a key protective factor in the psychological adjustment of individuals to traumatic events. However, since March 2020, extant research has revealed evidence of increased loneliness, social isolation, and disconnection, likely due to COVID-19 pandemic-related recommendations that restricted day-to-day contact with others. Methods In this investigation, we applied a case-control design to test the direct impacts of the pandemic on social support in United States adults recovering from a significant injury caused by PTSD-qualifying, traumatic events (e.g., motor vehicle crashes, violence, etc.). We compared individuals who experienced trauma during the pandemic, the “cases” recruited and evaluated between December 2020 to April 2022, to trauma-exposed “controls,” recruited and evaluated pre-pandemic, from August 2018 through March 9, 2020 (prior to changes in public health recommendations in the region). Cohorts were matched on key demographics (age, sex, education, race/ethnicity, income) and injury severity variables. We tested to see if there were differences in reported social support over the first 5 months of adjustment, considering variable operationalizations of social support from social network size to social constraints in disclosure. Next, we tested to see if the protective role of social support in psychological adjustment to trauma was moderated by cohort status to determine if the impacts of the pandemic extended to changes in the process of adjustment. Results The results of our analyses suggested that there were no significant cohort differences, meaning that whether prior to or during the pandemic, individuals reported similar levels of social support that were generally protective, and similar levels of psychological symptoms. However, there was some evidence of moderation by cohort status when examining the process of adjustment. Specifically, when examining symptoms of post-traumatic stress over time, individuals adjusting to traumatic events during COVID-19 received less benefit from social support. Discussion Although negative mental health implications of the pandemic are increasingly evident, it has not been clear how the pandemic impacted normative psychological adjustment processes. These results are one of the first direct tests of the impact of COVID-19 on longitudinal adjustment to trauma and suggest some minimal impacts.